Shear strength characteristics of an estuarine bed - Mahbubur Rahman,; Zawawi Sarnba Mohamed,; Jamal Mohd Amin, (1996)
Shear strength of estuarine low strength clay deposit is characterized by the interparticle bonds which must be broken to initiate erosion. The bonding strength is influenced by the physico-chemical factors prevailing in the estuarine environment. Successively incremental flow-induced bed shear stress is applied to induce layer by layer erosion of soft sediment deposit to determine the shear strength. Thickness of each eroding layer is noted. In general, shear strength τ s increases with depth. Salinity and bed consolidation period influence the shear strength behavior. A sudden decrease in erosion rate was observed for a greater value of characteristic shear stress